x-2(x-3分之a)

职业培训 培训职业 2025-01-02
3(x- 2(x- a/3))= 4x3(x- 2x+ 2a/3)= 4x3(-x+ 2a/3)= 4x-3x+ 2a= 4x2a= 7xx= 2a/7 3x/12+ a- 1/8- 5x= 1 x/4+ a- 1/8- 5x= 1-19x/4+ a= 9/8 把x= 2a/7代入,(-19/4)*(2a/7)+ a= 9/8-5a/14= 9/8a= -63/20 x=-9/10

3(x- 2(x- a/3))= 4x

3(x- 2x+ 2a/3)= 4x

3(-x+ 2a/3)= 4x

-3x+ 2a= 4x

2a= 7x

x= 2a/7

3x/12+ a- 1/8- 5x= 1

x/4+ a- 1/8- 5x= 1

-19x/4+ a= 9/8

把x= 2a/7代入,

(-19/4)*(2a/7)+ a= 9/8

-5a/14= 9/8

a= -63/20

x=-9/10

标签

版权声明:本文由哟品培原创或收集发布,如需转载请注明出处。

本文链接:http://www.yopinpei.com/20250102/2/1123874

猜你喜欢
其他标签